Cybercrime during the SARS-CoV-2 pandemic (2019-2022) - Ventre, Daniel; Loiseau, Hugo 1974- (ISTE, Ltd., 2023)
The SARS-CoV-2 pandemic has had an undeniable impact on cybercrime. The initial crisis quickly became a global catastrophe with multiple consequences in economics, health, and political and social fields. This book explores how this global emergency has influenced cybercrime. Indeed, since feeding off new vulnerabilities, thanks to the effects of the pandemic crisis in various states around the world, cybercrime has increased and evolved.
Online resource; title from PDF title page (John Wiley, viewed July 25, 2023)
Keywords: Computer crimes; COVID-19 Pandemic, 2020-; Computer security; COVID-19 Pandemic; (2020-); Since 2020; Criminalité informatique; Pandémie de COVID-19, 2020-; Sécurité informatique